Impact of Bidirectional Semiconductor Devices on DC and Hybrid Microgrids Enhanced by Wide Bandgap Materials - Abdul Waheed; Saif ur Rahman; Raheem Sarwar (Engineering Reports, 2025)
ABSTRACT Electric vehicles (EVs) are emerging as a leading option for traveling while considering the reduction in greenhouse gases (GHG) and corresponding expenditure of fossil fuels. Besides, microgrid (MG) operations pave the way for the development of renewable resources (RRs) based EV charging stations. The paper presents charging circuitry for EVs, designed with a two‐stage conversion mechanism, DC‐DC and hybrid grid in the MATLAB (SIMULINK) environment while using wide bandgap (WBG) semiconductors (SCs) like IGBTs and MESFETs. Power flow in DC and Hybrid‐microgrid (HMG) is supplied with the help of an isolated bidirectional battery charger with the potential of 1.5 kW at 120 V. The AC‐DC conversion is achieved through an inverter, while the rectification mechanism is used for DC‐DC conversion. The designed circuitry also employs four switches, operating at a high frequency, used with a PI controller to maintain the output of 120 V DC for battery charging. The remaining two controllers in the presented circuitry are used for the discharge system of the battery. The paper also presents a detailed comparative analysis of the conduction losses, measured for EV integration and future interventions while considering WBG‐SCs. The examination of the achieved results reveals that minimum losses are in the case of the DC grid system. The investigation of the results also shows lesser harmonic distortion for the DC grid in contrast to the other considered case. Results underline the insinuations of substance‐synchronized EV charging to condense adversative functioning impacts and associated ventures.